Kualitas Pelayanan Pengurusan Kartu Identitas Anak di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Karo - Tarigan, Eva Riyanti; Wulandari, Novita; Simamora, Beltahmamero (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2024)
This paper analyzes the quality of Child Identity Card management services at the Karo Regency Population and Civil Registration Office. Referring to the theoretical framework of Zeithaml, Parasuraman, and Berry, this study evaluates five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy. Data was collected through various methods such as observation, interviews, and documentation, then analyzed qualitatively. Research shows that services in Disdukcapil Karo Regency have reached optimal levels, but there are still shortcomings in several aspects such as the appearance and comfort of employees and speed of service. Supporting factors include quality human resources and innovation, while constraints are mainly related to lack of facilities, infrastructure, and personnel. This research provides valuable insights to improve the effectiveness of services at the institution